Monitoring and Evaluating Government Performance in Botswana - E. K. Botlhale (Africa’s Public Service Delivery & Performance Review, 2015)
In an era characterised by fiscal stress in the post-global recession era, clichés such as ‘bang for the buck’ are commonplace. Governments are under increasing pressure to spend limited public resources in efficient and  effective ways. Efficient and  effective governments are a necessary, though not sufficient, condition for economic development. Hence, governments have adopted performance-improving interventions such as New Public Management. Botswana jumped into the bandwagon of public sector reforms in the 1990s through interventions such as Performance-based Management Systems. The focus was almost entirely on performance enhancement to the neglect of performance measurement through a result-based Monitoring and Evaluation (M&E) framework. However, in 2009, the government decided to mainstream M&E into the development planning regime. Since the M&E tool is still in draft form, Botswana is very favourably circumstanced to learn from others. Meanwhile essentials to do are: attitudinal change, shared vision on M&E, stakeholder management and demand and use of M&E information by policy-makers such as Members of Parliament.